2015
DOI: 10.1128/jcm.01387-15
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Cervical Microflora Dominated by Lactobacillus iners in Korean Women

Abstract: cLactobacillus spp. are associated with the maintenance of reproductive health, but obesity reduces fertility and is a risk factor for obstetric and neonatal complications. We assessed the association between obesity and the cervical Lactobacillus composition, which has not been examined previously. Pyrosequencing was performed using cervical swabs collected from 76 normal participants with negative results for cervical intraepithelial neoplasia (CIN) and 57 participants with CIN, based on histological examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
2
25
0
8
Order By: Relevance
“…35,36 Although these studies suggest that there may be an increased prevalence of BV in overweight/obese women, participant BV status was not reported. 33,34 One study conducted among US women reported a positive correlation between high BMI and BV; however, after multivariable modeling, this study showed BMI was not associated independently with BV. 37 This study had several caveats that included that less than one-third of the women who were examined were black, and that it did not examine the relationship between BMI and women with an "intermediate" microbiota (Nugent score,4e6).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…35,36 Although these studies suggest that there may be an increased prevalence of BV in overweight/obese women, participant BV status was not reported. 33,34 One study conducted among US women reported a positive correlation between high BMI and BV; however, after multivariable modeling, this study showed BMI was not associated independently with BV. 37 This study had several caveats that included that less than one-third of the women who were examined were black, and that it did not examine the relationship between BMI and women with an "intermediate" microbiota (Nugent score,4e6).…”
mentioning
confidence: 57%
“…Most recently, it has been reported that the vaginal microbiota of overweight and obese Korean women exhibited a larger proportion of L iners and Prevotella compared with lean women. 33,34 This is of interest because both of these taxa previously have been associated with BV. 35,36 Although these studies suggest that there may be an increased prevalence of BV in overweight/obese women, participant BV status was not reported.…”
mentioning
confidence: 99%
“…Studies have also linked obesity to early‐onset GBS infection in neonates . Differences have been identified in the vaginal and gut microbiome between women who are obese and women of normal weight, with emerging evidence of a causal association between the gut microbiome and obesity . As such, the factors that are driving the population rise in obesity may also serve to drive increases in GBS colonisation, and in turn early‐onset disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was limited to the analysis of interrelationships between cervical Lactobacillus species only with non-Lactobacillus members of the microbiota not considered. Therefore the generalisability of these ndings are unclear [50]. Our ndings suggest an increased prevalence of Lactobacillus-depleted vaginal microbiome in obese women, with a greater mean proportion of Lactobacillus crispatus in non-obese compared to obese women (Figure 2d).…”
Section: Discussionmentioning
confidence: 76%